Matriconditioning on physiological performance of amaranth seeds - Witkovski, Adriane; Stefeni, Alberto Ricardo; Possenti, Jean Carlo; Lima, Adriana Bezerra de; Deuner, Cristiane (Scientia Agraria Paranaensis, 2020)
Matriconditioning is a technique that aims to standardize and accelerate the germination of seeds and the emergence of plantlets. The objective of the study is to evaluate the effect of that methodology under the physiological performance of amaranth seeds. The experiment used two lots of seeds at the Universidade Tecnológica Federal do Paraná (UTFPR), Campus Dois Vizinhos (Parana State). Plastic boxes of the Gerbox type were the matriconditioning environment, containing 55.5 g of sterile vermiculite moisturized with distilled water at 100% of the retention capacity. Plastic boxes were placed in a germination chamber at ten degrees Celcius. Four repetitions of 100 seeds had their weight measured at 0, 2, 4, 8, 16, and 32 h after the procedure started to obtain the curve of imbibition. The following tests were performed after each period: Germination test, first germination count; length and dry mass of plantlets; emergence speed index, and accumulated emergence tests. Amaranth seeds achieve phase II of germination around 8 h of imbibition by matriconditioning. The effect of matriconditioning in the physiological performance of amaranth seeds varies as a function of the used lot.